The Culture Dish Surface Influences the Phenotype and Cytokine Production of Human Monocyte-Derived Dendritic Cells - Sauter, Alexander; Yi, Dag Heiro; Li, Yayan; Roersma, Sabine; Appel, Silke (Frontiers in Immunology, 2019)
Monocyte-derived dendritic cells (moDC) are an important scientific and clinical source of functional dendritic cells (DC). However, the optimization of the generation process has to date mainly been limited to the variation of soluble factors. In this study, we investigated the impact of the cell culture surface on phenotype and cytokine profile. We compared a standard cell culture dish to a non-adherent culture dish for two immunogenic maturation conditions, two tolerogenic conditions and an unstimulated control. Phenotype, cytokine profile and T cell stimulatory capacity were determined after a 3-day culture. Light microscopy revealed an increase in homotypic cluster formation correlated with the use of non-adherent surfaces, which could be reduced by using blocking antibodies against CD18. All surface markers analyzed showed moderate to strong differences depending on the culture dish surface, including significantly decreased expression of key maturation markers such as CD80, CD86 and CCR7 as well as PD-L1 on cells stimulated with the Jonuleit cytokine cocktail cultured on a non-adherent surface. Significant differences in the secretion of many cytokines were observed, especially for cells stimulated with LPS, with over 10-fold decreased secretion of IL-10, IL12-p40 and TNF-α from the cells cultured on the non-adherent surface. All immunogenic moDC populations showed similar capacity to induce antigen-specific T cells. These results provide evidence that the DC phenotype depends on the surface used during moDC generation. This has important implications for the optimization of DC-based immunotherapy development and underlines that the local surrounding can interfere with the final DC population beyond the soluble factors.